Development of Village-Owned Enterprises (BUMDes) in Bintan Regency Through Collaborative Governance - Afrizal, Afrizal; Kustiawan, Kustiawan; Nazaki, Nazaki; Paramitha, Anggia (Journal of Governance, 2024)
Village-Owned Enterprises (BUMDes) are one of the programs of the government of the Republic of Indonesia to improve the welfare of village communities. BUMDes is expected to be able to change the economic conditions of village communities, the majority of which are poor, towards economic stability. According to data from BPS in 2020, the majority of poor people in Indonesia are at 60%. BUMDes that are successful in their management are proven to be able to provide economic benefits to village communities and village governments by providing income in the form of PADes. BUMDes that have innovation in their management provide benefits for Indonesia's development, which builds society starting from the village. One of the innovations in developing BUMDes is through government cooperation or Collaborative Governance. BUMDes in Bintan Regency, Riau Islands Province which implements Collaborative Governance and is proven to be able to increase BUMDes income. This research wants to find out and explain how the implementation of BUMDes Collaborative Governance in Bintan Regency towards independent BUMDes improves the economy of village communities.